Building an electromechanical robotic structure of wall-e - Alam, Md. Firoz; Saha, Gourab Kishore; Sundrin, Tanzid Nahid Mustafa; Choudhury, Zakir Hasan (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.